Annealing strengthening in a dilute Mg–Zn–Ca sheet alloy. (October 2015) - Zeng, Z.R.; Zhu, Y.M.; Bian, M.Z.; Xu, S.W.; Davies, C.H.J.; Birbilis, N.; Nie, J.F.
Graphical abstract: Abstract: Magnesium sheet alloy of dilute composition, Mg–0.3Zn–0.1Ca (at.%), does not exhibit any hardening response during heating. However, an annealing treatment at 80–200 °C, after some plastic strain in tension, leads to a remarkable strengthening, rather than softening, effect. By using electron backscattered diffraction and scanning transmission electron microscopy, it is found that the strengthening effect is caused by the pinning of gliding basal dislocations by GP zones and possibly solute atoms segregated to the dislocations.